Determinants of Catch And Catch Per Unit Effort Of Motorboat And Outboard Motorboat Fishers In Bulukumba Regency - Nurasri Mulyani; Abd. Rahim; Diah Retno Dwi Hastuti; Citra Ayni Kamaruddin (Demeter: Journal of Farming and Agriculture, 2024)
Motor and outboard boats are the main means by which fishersmen exploit the fisheries resources in these waters. The success of the catch and the efficiency of the fishermen's efforts are strongly influenced by various factors related to the characteristics of the boat, the fishing gear and the condition of the aquatic environment. This study aims to analyse the determinants of catch and catch per unit effort of motorboat and outboard motorboat fishers in bulukumba regency. Data collection techniques used were observation, interview and documentation. The number of samples was 81 modern fishermen (juragan fishermen) of motorboats out of 407 population using the Slovin formula method and 81 outboard motorboat fishermen out of 81 population using the area proportional random sampling method. Data analysis techniques used are statistical tests, classical assumptions tests using SPSS 25 and CPUE analysis. The study found that the length of fishing (X1), volume of diesel (X2), age of fishermen (X4), and fishing experience (X6) had a positive impact on the production of motorboat fishermen's catch (Y1) when examined independently. On the other hand, the number of labour (X3) and formal education of fishermen (X5) were negatively correlated with catch production. The duration of sea time (X7) and the power of the outboard engine (X8) have a positive impact, whereas the volume of petrol (X9), age of fishermen (X10), formal education of fishermen (X11), sea experience (X12), and number of fishing gear used (X13) have a negative impact on the catch rate of outboard motorboat fishermen (Y2). Based on the CPUE (Catch per Unit Effort) value, there has been a fluctuation of motorboat and outboard motorboat fishermen from 2017 to 2021. The average value per year, from 2017 to 2021, was 389.9914kg/trip for motorboat fishermen and 46.66028kg/trip for outboard motorboats. It is recommended to increase the number of fishing gear, particularly trawl gear, and transportation facilities in fishing. Fishers should be incentivised to utilise fishing equipment that is appropriate for the specific kind of fish and local aquatic environments in order to enhance catches and reduce negative impacts on fishing resources.